Analisis Pola Fungsi Kalimat Tunggal Teks Berita Daring Kemdikbud Jelita Edisi Oktober 2023 sebagai Sumber Bacaan Siswa Kelas X SMA - Febriyani Kusumaningrum; Azhar Aji Winanda; Lintang Kusumaningrat; Deane Rahmah Indriawati; Rahma Safitri; Asep Puwo Yudi Utomo; Mursito Mursito (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
With the existence of online news, students are considered to have easy access to information. Not only as a part of the material but also as learning resources for 10th-grade high school students. This research aims to determine the effectiveness of the function patterns of simple sentences in the online news texts of Kemdikbud Jelita as a reading source for 10th-grade high school students. The approach used in this study is a descriptive approach, which involves analyzing the function patterns of simple sentences. A qualitative descriptive method was employed. The researcher used the note-taking and observation technique on Kemdikbud Jelita's online news texts to understand their content. The researcher also recorded the patterns of simple sentences found in the news texts using the distributional method. From the data analysis conducted, it was found that there were 50 simple sentences in the Kemdikbud Jelita news that had easily understood functional patterns for 10th-grade high school students as a reading source. The results of the analysis in this article can deepen the understanding of sentence function patterns and their appropriateness as a reading source for 10th-grade high school students. The sentence patterns and their usage can provide guidance for educators and material developers to improve the quality of reading sources.